Combined source infrastructure assessment model - Maurer, Anne, author; Sale, Tom, advisor; Bau, Domenico, committee member; Sanford, William, committee member (Colorado State University. Libraries, 2012)
Integrated utilization of surface and groundwater is a promising strategy that has the potential to reduce the costs associated with water system infrastructure projects and improve the sustainability of yields from finite water resources. Planning and design of conjunctive use systems can be complicated. Key challenges include resolving the timing of withdrawals, timing of storage, sizing of infrastructure components, and efficiently estimating costs. A combined source infrastructure assessment model (CSIAM) has been developed in this study using a decision programming approach. The CSIAM is designed for single-and multi-source water systems including surface water-only, groundwater-only, and combined surface water and groundwater sources. Aquifer Storage and Recovery (ASR) via groundwater injection wells is a primary component of the CSIAM when there is surplus surface water available to store. Primary model inputs include project life-span, per capita demands, initial population, population growth rate, surface water treatment capacity, number of existing wells, inflows, reservoir stage-storage, evaporative and seepage losses, and unit costs for capital expenditures and operations and maintenance. Model outputs include project water demands, surface reservoir storage, volume of monthly surface water treatment, groundwater extraction and/or injection volumes, cumulative groundwater extraction and/or injection volumes, number of wells, capital costs, operation and maintenance costs, life-cycle costs, and present value. The model is demonstrated via analysis of three scenarios involving groundwater-only, combined groundwater and surface water, and surface water-only. The scenarios are predicated on data provided by the town of Castle Rock, Colorado. While the Town of Castle Rock provides a basis for applying the model, the results should not be viewed as having direct bearing on future actions in the Town of Castle Rock. Many of the key issues that will ultimately drive the Town's water supply plans are not included in this analysis. Use of a combined groundwater and surface water system is $91 million and $231 million less than a groundwater-only system and streamflow-only system, respectively. Furthermore, the use of a combined groundwater and surface water system reduces groundwater depletion by 55%, relative to a groundwater-only system. In addition, a total of 107 pumping wells will need to be installed in a groundwater-only system versus 67 pumping wells in a combined groundwater/surface water system. Both deterministic and stochastic inputs are used in the model, wherein the principle stochastic input is urban irrigation demands. The differences between results using deterministic and stochastic inputs vary depending on the output. In general, analyses using stochastic inputs lead to a need for infrastructure with greater capacities and higher costs. The CSIAM also can be used to resolve costs as a function of groundwater depletion by testing different surface water treatment plant sizes.
Keywords: aquifer storage and recovery; conjunctive use; cost model; groundwater; water sustainability; water system infrastructure